Heterosis and combining ability for grain yield and its contributing characters in maize - Alam, AKMM; Ahmed, S; Begum, M; Sultan, MK (Bangladesh Journal of Agricultural Research, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Combining ability analysis for grain yield and its contributing characters in maize were carried out in 5Ã5 diallel cross. The highest percentage of heterosis for grain per ear over mid parent and better parent were observed by the cross P2ÃP3. Crosses P1ÃP3 and P1ÃP5 showed significant negative heterosis for days to maturity. Significant general and specific combining ability variances were observed for all the characters except ear height. Almost equal role of additive and non-additive gene actions was observed for days to maturity. Additive genetic variance was preponderant for grains per ear and 1000-grain weight and non-additive gene action was involved in plant height, ear height, days to silking, and days to maturity. The inbred lines P2 and P5 were found to be best general combiner for 1000-grain weight. Key Words: Heterosis, combining ability, grain yield, maize. doi:10.3329/bjar.v33i3.1596 Bangladesh J. Agril. Res. 33(3) : 375-379, September 2008